2011
DOI: 10.1175/2011mwr3632.1
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Convective-Scale Background Error Covariances with the Inclusion of Hydrometeor Variables

Abstract: Convective-scale models used in NWP nowadays include detailed realistic parameterization for the representation of cloud and precipitation processes. Yet they still lack advanced data assimilation schemes able to efficiently use observations to initialize hydrometeor fields. This challenging task may benefit from a better understanding of the statistical structure of background errors in precipitating areas for both traditional and hydrometeor variables, which is the goal of this study. A special binning has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 65 publications
(80 reference statements)
6
87
1
Order By: Relevance
“…2, is quite consistent with the findings of Michel et al (2011) andBrousseau et al (2012). This temperature background error shape in AROME-France for the lowest levels is due to the estimation of the error covariances, which occurred during a period with more anticyclonic and stable meteorological conditions than that of the AROME-WMED.…”
Section: Background Error Statisticssupporting
confidence: 86%
See 1 more Smart Citation
“…2, is quite consistent with the findings of Michel et al (2011) andBrousseau et al (2012). This temperature background error shape in AROME-France for the lowest levels is due to the estimation of the error covariances, which occurred during a period with more anticyclonic and stable meteorological conditions than that of the AROME-WMED.…”
Section: Background Error Statisticssupporting
confidence: 86%
“…Several studies have indeed demonstrated the strong dependence of the background error statistics on weather regimes. For instance, using the Weather Research and Forecasting (WRF) model at 3 km resolution, Michel et al (2011) showed that the specific humidity standard deviation of the model background error is larger in rain affected areas than in non-rainy conditions.…”
Section: Background Error Statisticsmentioning
confidence: 99%
“…The extension of the control variable to hydrometeors and the possible direct assimilation of quantities provided by polarimetric radars need to be considered in the future. Michel et al (2011) have estimated the covariance errors for hydrometeors, which is a first step in that direction.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Michel et al (2011) points out such problems and suggests the use of an ensemble of shortrange forecasts at high resolution to estimate the background-error covariances (including hydrometeor variables). They propose heterogeneous covariances as a way to separate rainy and nonrainy areas.…”
Section: Introductionmentioning
confidence: 99%
“…In order to get insights into the processes that may be involved in NG development, the diagnostics have been separately computed for cloudy and for clear sky areas, following a similar approach to that of Montmerle and Berre (2010) and Michel et al (2011), in which precipitating masks have been used. Grid points over the domain are separated in two bins: "cloudy" or "clear-sky" points.…”
Section: Time Evolution Of Non-gaussianitymentioning
confidence: 99%